(3eUfa YHO GdQRGbs - (3YHO GdQGRb Hf geGe GdUZGfjs
(3ChdgG (B:s
(3jHJOF HHGH eJi jaWQ GdeSde Mjf jNQL eSGaQkG s
(3BNQgG (B:s
(3jfJgi HHGH GdhHQ hGdVHi jbJdgG GdeMQe ef cJGH GdML s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1712s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs